Can Electronic Word of Mouth Mediate the Relationship between Omnichannel and Purchase Intention? Retail Company? - Ainaya Mutia; Muhammad Mujahid Dakwah; Sri Maryanti (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of omnichannel marketing on purchase intention at Alfamart, with electronic word of mouth as a mediating variable. The study used quantitative methods with a sample size of 152 respondents.Data were collected through an online questionnaire using a five-point Likert scale to measure omnichannel, purchase intention, and electronic word of mouth.Structural Equation Modeling approach based on Partial Least Squares (PLS-SEM) with SmartPLS 4.0 software was used toproduces information related to the Loading Factor, Composite Reliability, Average Variance Extracted (AVE) values, and Hypothesis Testing Output both directly and indirectly. The results of the study indicate that all relationships between variables are proven positive and significant. Omnichannel has a positive and significant effect on purchase intention (T-Statistic = 3.805; P-Values ​​= 0.000), omnichannel has a positive and significant effect on E-WOM (T-Statistic = 11.133; P-Values ​​= 0.000). In addition, E-WOM also has a positive and significant effect on purchase intention (T-Statistic = 4.277; P-Values ​​= 0.000). Mediation analysis shows that E-WOM positively and significantly mediates the effect of omnichannel on purchase intention (T-Statistic = 3.834; P-Values ​​= 0.000). These findings indicate that effective omnichannel implementation not only directly increases purchase intention but also encourages the formation of digital reviews and recommendations, further strengthening purchase intention at Alfamart. Based on the research results and implications, several recommendations can be made for future research, including expanding the research object to various types of retail outlets, adding mediating variables, and combining research methods to provide more accurate respondent information. Omnichannel integration needs to be continuously optimized so that consumers can move seamlessly between physical stores and digital channels. Practically, companies need to improve the quality of digital services, such as easy access to product information, clarity of product availability, and ease of transactions, to encourage positive consumer reviews..